2015
DOI: 10.2965/jwet.2015.325
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Detoxicity of Tetracycline by an Enhanced Sonolysis

Abstract: Tetracycline is named by its four special benzene rings in molecular structure, which has been proven as a strong inhibition chemical for many kinds of bacterial. To solve the problem of residual tetracycline containing in municipal and medicine industrial wastewater effluents, this study tried to combine the ultrasound with transition metals ( .9% of tetracycline were degraded and mineralized. In addition, the toxicity was significantly reduced while the cell viability increased from 53.1% (un-treated) to 87.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…An in-depth overview of different Fenton processes, including single-Fenton and coupled-Fenton processes, reaction parameters optimization for wastewater treatment is reviewed by Zhang et al [39]. Classical Fenton or coupled-Fenton processes have been successfully applied to degrade TC, including photo-Fenton [34], sono-Fenton [40], and electro-Fenton process [41].…”
Section: Fenton Processmentioning
confidence: 99%
See 1 more Smart Citation
“…An in-depth overview of different Fenton processes, including single-Fenton and coupled-Fenton processes, reaction parameters optimization for wastewater treatment is reviewed by Zhang et al [39]. Classical Fenton or coupled-Fenton processes have been successfully applied to degrade TC, including photo-Fenton [34], sono-Fenton [40], and electro-Fenton process [41].…”
Section: Fenton Processmentioning
confidence: 99%
“…found to remove 93.6% TC within 60 min of reaction with 31.8% removal efficiency of TOC [52]. Wang et al reported more than 90.7% TC degradation when authors applied ultrasound to 0.2 mM Fe 2+ and 2 mM H 2 O 2 in a novel enhanced sonolysis process [40]. In a recent study, the mesoporous bimetallic Fe/Co catalyst was reported to degrade TC optimally (86% removal rate) at Fe to Co ratio of 2:1, pH 5-9, H 2 O 2 30 mmol, and initial TC concentration of 30 mg L −1 [53].…”
Section: Fenton Processmentioning
confidence: 99%
“…The degradation efficiency and TOC removal of the present method are significantly better than those of the other methods reported in the literature for the degradation of the TCH antibiotic as shown in Figure , and the details of the experimental conditions are shown in Table S1. …”
Section: Resultsmentioning
confidence: 68%
“…The degradation of amoxicillin and tetracycline was reported by this technique (Novak et al 2012;Safari et al 2015;Wang and Jian 2015). In the case of amoxicillin, the sulfate radicals are produced using ultrasound-activated oxone in the presence of cobalt ion.…”
Section: Addition Of Radical Promotermentioning
confidence: 97%